2015
DOI: 10.1017/s1478951515001108
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of communication-skills training interventions in end-of-life noncancer care in acute hospital-based services: A systematic review

Abstract: A note on versions:The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. Please see the 'permanent WRAP URL' above for details on accessing the published version and note that access may require a subscription For more information, please contact the WRAP Team at: wrap@warwick.ac.uk Significance of ResultsFurther research is needed to fully explore the effectiveness of existing training interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 33 publications
2
29
0
Order By: Relevance
“…Although poor reporting of outcome measurement 27 and study results 32 have previously been identified in this field, our comprehensive dataextraction process across 170 unique records details the extent of inadequate reporting of interventions and their evaluations ( Table 1). Lack of transparency in reporting is problematic, hindering progression in the field in two ways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although poor reporting of outcome measurement 27 and study results 32 have previously been identified in this field, our comprehensive dataextraction process across 170 unique records details the extent of inadequate reporting of interventions and their evaluations ( Table 1). Lack of transparency in reporting is problematic, hindering progression in the field in two ways.…”
Section: Discussionmentioning
confidence: 99%
“…8 However, there remains little consensus regarding optimal training strategies, the most effective teaching methods, and what constitutes an adequate ''dose'' of communication skills training. Although there has been some evidence synthesis in relation to EoLC communication training for specific staff groups (e.g., oncology, 30e33 noncancer care in acute settings 27 ), there has been no comprehensive consideration of the evidence regarding training interventions for all those involved in the delivery of generalist palliative care. This is required not just as a resource for clinical educators and researchers, but also to enable research in this field to progress.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the effects of training interventions on attitudinal changes of healthcare professionals were only concerned about shared decision-making, psychosocial care, and end-of-life care. (6,8) This study showed that training may also be associated with positive attitudes toward ACP.…”
Section: Discussionmentioning
confidence: 75%
“…(2,3) Certain training interventions have been developed to equip healthcare professionals with the skills to facilitate ACP, and the ndings showed that training was effective in improving professionals' knowledge, con dence, and communication skills in conducting ACP. (4)(5)(6)(7)(8) However, the effects of training on their attitudes toward ACP, which is crucial to the integration of ACP into routine care practices, has rarely been studied. This paper reports the association between healthcare professionals' attitudes toward ACP and relevant training experience based on secondary analysis of the ndings from an online survey.…”
Section: Introductionmentioning
confidence: 99%
“…23,[26][27][28][29] Third, data on impact of training interventions on the attitudinal barriers identified above are limited. [30][31][32] We need generalizable, scalable workforce training that addresses key barriers to clinician uptake.…”
mentioning
confidence: 99%